2008
DOI: 10.2174/138161208786848748
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Neuronal Damage

Abstract: Knowledge of the molecular mechanisms that underlie neuron death following stroke is important to allow the development of effective neuroprotective strategies. Since studies in human stroke are extremely limited due to the inability of collecting post mortem tissue at time points after the onset of stroke where neuronal death occurs, brain ischemia research focuses on information derived from animal models of ischemic injury. The two principal models for human stroke are induced in rodents either by global or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
1
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(84 citation statements)
references
References 0 publications
2
80
1
1
Order By: Relevance
“…Thus large amounts of ATP can be released into the extracellular space under pathological conditions such as tissue injury, cell lysis, and cell ischemia. 3,108 Under physiological conditions, cytosolic ATP can be released via transmembrane transport in response to receptor activation in both vascular smooth muscle cells and endothelial cells. 96,98,68,123 In most neurons, ATP is stored in vesicles with neurotransmitters and coreleased.…”
Section: +mentioning
confidence: 99%
“…Thus large amounts of ATP can be released into the extracellular space under pathological conditions such as tissue injury, cell lysis, and cell ischemia. 3,108 Under physiological conditions, cytosolic ATP can be released via transmembrane transport in response to receptor activation in both vascular smooth muscle cells and endothelial cells. 96,98,68,123 In most neurons, ATP is stored in vesicles with neurotransmitters and coreleased.…”
Section: +mentioning
confidence: 99%
“…The ionotropic glutamate receptors are NMDA receptors and AMPA receptors. The cerebral concentration of Glu and Asp can increase too high, which can overactivate the NMDA receptor that can cause various consequences, including the over-activation of protein kinases, endonucleases, phosphoglycerate kinase, and nitric oxide synthase, and the formation of peroxide, thus leading to the degradation of DNA and death of neurons (Taoufik and Probert, 2008). In the present study, we found that the excitatory amino acids Glu, Asp, and Gly increased significantly after DHCA, which was consistent with previous studies (Tseng et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive glutamate release is regarded as a trigger of neuronal cell damage during cerebral ischemia [20]. To examine whether KGKR acts directly on pre-synaptic glutamatergic neurons, we measured the effect of KGKR on glutamate release in the hippocampus.…”
Section: Discussionmentioning
confidence: 99%